Analisis Kompetensi Pedagogi Guru Pendidikan Agama Hindu Jenjang Sekolah Dasar Di Kabupaten Bangli - Wahyuni, Ni Nyoman Tri; Prima Dewi PF, Kadek Aria (Jurnal Penelitian Agama Hindu, 2024)
The teacher is one of the determining factors of education quality. A professional teacher understands and can apply four competencies: pedagogical, professional, social, and personal competencies. This study aims to describe and analyze the pedagogical competencies of Hindu Religion subject teachers at the Elementary School level in Bangli regency. This research is classified as quantitative descriptive research. The research instrument used was a questionnaire on pedagogical competency consisting of five indicators. Data were analyzed descriptively. The results of the study indicate that the pedagogical competency of Hindu Religion subject teachers at the Elementary School level in Bangli regency overall falls within the category of sufficient. Among the five indicators, the indicator of deep understanding of the subject taught is categorized as good, while the other indicators are categorized as sufficient. This research can serve as a reference for formulating models or strategies for developing the competencies of Hindu Religion and Ethics teachers.